1998
DOI: 10.1021/bi980828m
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B-100 Conformation and Particle Surface Charge in Human LDL Subspecies:  Implication for LDL Receptor Interaction

Abstract: The plasma low-density lipoprotein (LDL) profile in coronary artery disease patients is characterized by a predominance of small, dense LDL. Small, dense LDL exhibit both high susceptibility to oxidation and low binding affinity for the LDL receptor, suggesting that these particles may be of elevated atherogenic potential. Here we examine whether the variation in biological function is due to differences in apo B-100 conformation that alter the interaction with the cellular LDL receptor. The microenvironments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 46 publications
7
94
0
1
Order By: Relevance
“…This explanation would be expected from what is known of the mechanism by which statins lower LDLC, which involves an increase in hepatic LDL catabolism due to the up-regulation of LDL receptors (3,28,34,35 ). These receptors are known to have a greater affinity for larger, cholesterol-rich LDL particles than for smaller, cholesterol-depleted ones (36 ). The reports of a statin-induced decrease in small, dense LDL particles are thus likely to be predominantly due to a decrease in these particles' larger LDL precursor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation would be expected from what is known of the mechanism by which statins lower LDLC, which involves an increase in hepatic LDL catabolism due to the up-regulation of LDL receptors (3,28,34,35 ). These receptors are known to have a greater affinity for larger, cholesterol-rich LDL particles than for smaller, cholesterol-depleted ones (36 ). The reports of a statin-induced decrease in small, dense LDL particles are thus likely to be predominantly due to a decrease in these particles' larger LDL precursor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Increased LDL 3 is associated with increased rates of myocardial infarction (5-7). LDL 3 is more prone to oxidation and glycemic modification (23) and as a result does not bind as well to hepatic LDL receptors (24) and is more likely to bind to the extracellular matrix and be taken up by scavenger macrophages in atherosclerotic plaques (25)(26)(27).…”
Section: Effects Of Pioglitazone and Metforminmentioning
confidence: 99%
“…The altered conformation of apolipoprotein B-100 (apoB-100) in LDL À is a factor in its reduced binding to the LDL receptor (19). Whereas one study showed that the densest LDL subfrac-tions were richest in LDL À (18%) (20), another reported more LDL À in both sdLDL and buoyant LDL from hyperlipemic subjects (21).…”
mentioning
confidence: 99%